Mid-expiratory flow versus FEV1 measurements in the diagnosis of exercise induced asthma in elite athletes. Issue 2 (14th October 2005) - Dickinson, J W; Whyte, G P; McConnell, A K; Nevill, A M; Harries, M G
Abstract : Backround: A fall in FEV1 of ⩾10% following bronchoprovocation (eucapnic voluntary hyperventilation (EVH) or exercise) is regarded as the gold standard criterion for diagnosing exercise induced asthma (EIA) in athletes. Previous studies have suggested that mid-expiratory flow (FEF50 ) might be used to supplement FEV1 to improve the sensitivity and specificity of the diagnosis. A study was undertaken to investigate the response of FEF50 following EVH or exercise challenges in elite athletes as an adjunct to FEV1 . Methods: Sixty six male (36 asthmatic, 30 non-asthmatic) and 50 female (24 asthmatic, 26 non-asthmatic) elite athletes volunteered for the study. Maximal voluntary flow-volume loops were measured before and 3, 5, 10, and 15 minutes after stopping EVH or exercise. A fall in FEV1 of ⩾10% and a fall in FEF50 of ⩾26% were used as the cut off criteria for identification of EIA. Results: There was a strong correlation between ΔFEV1 and ΔFEF50 following bronchoprovocation ( r  = 0.94, p = 0.000). Sixty athletes had a fall in FEV1 of ⩾10% leading to the diagnosis of EIA. Using the FEF50 criterion alone led to 21 (35%) of these asthmatic athletes receiving a false negative diagnosis. The lowest fall in FEF50 in an athlete with a ⩾10% fall in FEV1 was 14.3%. Reducing the FEF50 criteria to ⩾14% led to 13 athletes receiving a false positive diagnosis. Only one athlete had a fall in FEF50 of ⩾26% in the absence of a fall in FEV1 of ⩾10% (ΔFEV1  = 8.9%). Conclusion: The inclusion of FEF50 in the diagnosis of EIA in elite athletes reduces the sensitivity and does not enhance the sensitivity or specificity of the diagnosis. The use of FEF50 alone is insufficiently sensitive to diagnose EIA reliably in elite athletes.